2019
DOI: 10.1186/s12904-019-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

Discussing end of life wishes – the impact of community interventions?

Abstract: Background Many people do not discuss end of life preferences with those closest to them, although this can be beneficial to the individual and wider population. This study evaluated a community intervention to promote end of life preparation and discussion among people who are currently well. Methods A series of presentations and workshops (the intervention) were delivered to community groups and people working within health and social care. Participants were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…There are few studies on information meetings [17,23], and we did not find previous studies of end-of-life information meetings initiated by GPs. The information meetings were held by GPs from four different group practices.…”
Section: Strengths and Limitations Of This Studycontrasting
confidence: 65%
See 1 more Smart Citation
“…There are few studies on information meetings [17,23], and we did not find previous studies of end-of-life information meetings initiated by GPs. The information meetings were held by GPs from four different group practices.…”
Section: Strengths and Limitations Of This Studycontrasting
confidence: 65%
“…The meetings seem to be a time efficient way to stimulate ACP conversations with the GP and others. A recent study on two public health interventions (‘Awareness-Raising’ presentations and ‘How to’ workshops) also yielded positive results with regard to stimulating discussions [ 17 ]. The GPs did not receive a remuneration for organising these meetings.…”
Section: Discussionmentioning
confidence: 99%
“… Zwakman and colleagues (2018) found that participants with life-limiting illnesses suggested that ACP should take place sooner rather than later, to be experienced as less confrontational and therefore easier to accept. Recent studies have pointed to benefits in designing early, community-based interventions targeting people prior to diagnosis with life-limiting illnesses ( Abba, Lloyd-Williams, & Horton, 2019 ; Banner et al, 2019 ; Costello, Hinderer, Lee, & Chike-Udegha, 2015 ).…”
mentioning
confidence: 99%
“…14 Certain predictors to EOL discussions have been identified in the literature such as educational level, 20 living with a partner or other caregiver, 21 religiosity, [22][23][24][25][26] pain intensity, 21,27,28 older age, 29 and community activities. 29 However, limited research exists about the predictors for EOL discussions of minority older PLWH, particularly Black and Hispanic women. 30 Determining significant predictors may help guide future efforts to improve EOL discussions among these women.…”
Section: Introductionmentioning
confidence: 99%